Anthropological microcosm of university everyday life in the era of the late USSR (1970s-1980s): towards the formulation of the problem (by the example of the scientific community in the steppe region) - E. N. Badmaeva; E. U. Omakaeva (Nomadic Civilization: Historical Research)
The study is based on documentation of the late Soviet experience, theoretical generalization and interpretation of empirical data and archival documents. The phenomenon of a university as a set of incarnations of all members of the university community, aggregated in a certain way, is currently one of the most important scientific topics, but this issue, for all its relevance, has not yet received proper development and requires close attention from researchers.The article presented by us is aimed at analyzing the anthropological microworld of university everyday life in the 1970–1980s, which contains such criteria as the disclosure of a person’s potential, the possibility of realizing the tasks set by the state and the leading party for the individual and society in the socio-political conditions of the late Soviet era. The study examines the value parameters that characterize the teaching staff: motivation for work, attitude towards colleagues, as well as their ability to develop a vision of the role of the economy and other significant factors in everyday life: personal, collective, Soviet society, the country as a whole, etc.The study of the university topic is interesting for the possibility of creating a local version of the collective past of the late Soviet era, describing the atmosphere of that time, lifestyle, mentality, stereotypes of consciousness, and the peculiarities of the mentality of a Soviet person. The study of the scientific and educational team as a specific, original and unique “human” community involves the fixation and analysis of the existing relationships and interactions that unite university society.